The Comparison of the Strength of the Arm Muscle between the Conventional Basket Ball Training and the Training Using the Medicine Ball - Ida Ayu Kade Arisanthi Dewi (Journal of Global Pharma Technology, 2019)
The training for athletes in the basketball sports must have the excellent biomotor skills, especially in the components of the strength of the arm muscle to be able to do the passing and shooting with the maximum movement. The basketball game uses three main elements namely passing and catching, dribling, and shooting. Until now, the training technique in order to maximize the function of the arm muscle is carried out by loading sand in the body weighing 0.5 kg. This training technique is felt to be uncomfortable when moving, thus another technique is needed to perfect it, namely the training with the medicine ball. This research is a quasi-experimental study using the randomized pre and posttest control group design. The results show that the comparison of athlete's arm muscle strength levels using the conventional training technique with the medicine ball in a row, with the result of 21.45 : 42.3, i.e., there is an increase in the strength of the arm muscle by 49.29% in the medicine ball training. The training by using the medicine ball is an exercise plan using a 1.7-kg medicine ball which can improve the conventional training method.